2011
DOI: 10.1093/aob/mcr194
|View full text |Cite
|
Sign up to set email alerts
|

Centennial olive trees as a reservoir of genetic diversity

Abstract: This study of ancient olives has been fruitful both for germplasm collection and for enlarging our knowledge about olive domestication. The findings suggest that grafting pre-existing wild olives with olive cultivars was linked to the beginnings of olive growing. Additionally, the low number of genotypes identified in current cultivars points out that the ancient olives from southern Spain constitute a priceless reservoir of genetic diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 57 publications
15
90
1
4
Order By: Relevance
“…Of the old olive trees analyzed, scions of 252 trees were assigned to MLL-1 (Figure 4; Additional file 2); the bimodal frequency distribution of genetic distances among scions (Figure 3B) suggests that much of the diversity found among scions (Table 2) is due to somatic mutations. This implies that the substantial genetic diversity in the one dominant clone has accumulated during its probably very long existence, as had also been suggested for other ancient olive cultivars [13,18]. Although the diversity found in MLL-1 may be indicative of the antiquity of this ancestral clone, we unfortunately cannot even estimate the age of the trees, as in most cases the old inner parts of the trunks have disintegrated and are not available for radiocarbon dating or dendrochronological analysis.…”
Section: Discussionmentioning
confidence: 63%
“…Of the old olive trees analyzed, scions of 252 trees were assigned to MLL-1 (Figure 4; Additional file 2); the bimodal frequency distribution of genetic distances among scions (Figure 3B) suggests that much of the diversity found among scions (Table 2) is due to somatic mutations. This implies that the substantial genetic diversity in the one dominant clone has accumulated during its probably very long existence, as had also been suggested for other ancient olive cultivars [13,18]. Although the diversity found in MLL-1 may be indicative of the antiquity of this ancestral clone, we unfortunately cannot even estimate the age of the trees, as in most cases the old inner parts of the trunks have disintegrated and are not available for radiocarbon dating or dendrochronological analysis.…”
Section: Discussionmentioning
confidence: 63%
“…sylvestris ). Similarly, a recent genetic survey of scions and rootstocks of old olive trees in the Iberian Peninsula suggested that old olive trees were grafted on wild growing trees [35]. Based on the distances between grafted trees and their spatial arrangement within the groves, Diez et al [35] additionally suggested that natural forests were transformed into olive orchards by grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, various types of molecular markers have been widely used to distinguish between olive varieties, determine cultivars origin and to study the genetic diversity (De Caraffa et al, 2002;Rao Durgac et al, 2010;Rekik et al, 2008). Among these molecular markers, Microsatellites are one of the most used for olive genotyping and cultivars discrimination (Diaz et al, 2006Sarri et al, 2006Baldoni et al, 2009;Bracci et al, 2009;Erre et al, 2010;Díez et al, 2011;Fendrin et al, 2014;Linos et al, 2014). Moreover, SSR markers are suited to distinguish closely related genotypes because of their high degree of variability and multi-allelic states.…”
Section: Introductionmentioning
confidence: 99%